2012
DOI: 10.1029/2011jf002079
|View full text |Cite
|
Sign up to set email alerts
|

Backwater and river plume controls on scour upstream of river mouths: Implications for fluvio‐deltaic morphodynamics

Abstract: [1] Sediment flux from rivers to oceans is the fundamental driver of fluvio-deltaic morphodynamics and continental margin sedimentation, yet sediment transport across the river-to-marine boundary is poorly understood. Coastal rivers typically are affected by backwater, a zone of spatially decelerating flow that is transitional between normal flow upstream and the offshore river plume. Flow deceleration in the backwater zone, as well as spreading of the offshore plume, should render rivers highly depositional n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
259
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 172 publications
(282 citation statements)
references
References 93 publications
22
259
1
Order By: Relevance
“…Both of these effects should lead to a zone of preferential avulsion some distance upstream from the river mouth that scales with the backwater length. Following Bresse [1860], Lamb et al [2012] showed that for highly subcritical flows (Fr ≪1, where Fr is the Froude number), the maximum upstream length influenced by drawdown is 0.5 h n /S where h n is normal flow depth, whereas the maximum extent of backwater at low flows is h s /S where h s is the depth at the shoreline. Because avulsions are one of the main controls on delta evolution, these scaling relationships explain why delta lobes are more extensive in deep, low gradient rivers (e.g., Figure 1), and they provide a means for estimating delta response to perturbations that affect flow depth, channel depth at the shoreline, and channel slope (e.g., climate-induced changes in river discharge, sea level or sediment supply) [e.g., Jerolmack, 2009].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both of these effects should lead to a zone of preferential avulsion some distance upstream from the river mouth that scales with the backwater length. Following Bresse [1860], Lamb et al [2012] showed that for highly subcritical flows (Fr ≪1, where Fr is the Froude number), the maximum upstream length influenced by drawdown is 0.5 h n /S where h n is normal flow depth, whereas the maximum extent of backwater at low flows is h s /S where h s is the depth at the shoreline. Because avulsions are one of the main controls on delta evolution, these scaling relationships explain why delta lobes are more extensive in deep, low gradient rivers (e.g., Figure 1), and they provide a means for estimating delta response to perturbations that affect flow depth, channel depth at the shoreline, and channel slope (e.g., climate-induced changes in river discharge, sea level or sediment supply) [e.g., Jerolmack, 2009].…”
Section: Discussionmentioning
confidence: 99%
“…Most previous models for fluvio-deltaic evolution neglect backwater dynamics either by assuming uniform flow [e.g., Flemings and Jordan, 1989;Swenson et al, 2005] or a single characteristic river discharge [e.g., Parker et al, 2008], which prevents the backwater zone from being dynamic [Lamb et al, 2012]. Herein, we solve the 1-D non-uniform shallow-water flow equations for conservation of fluid mass and momentum [Chow, 1959] (auxiliary material (Text S1, section S2)).…”
Section: Model Goal and Formulationmentioning
confidence: 99%
“…Fast flows during low tide triggered by the drawdown water surface profile [Lamb et al, 2012] transport sediments to the sides, increasing the width of the depositional area. Tidal oscillations therefore act as a dispersion process similarly to waves [Jerolmack and Swenson, 2007;Nardin and Fagherazzi, 2012;Nardin et al, 2013].…”
Section: Discussionmentioning
confidence: 99%
“…Both the adverse bed slope and topographic relief at this bifurcation should limit sand transport into the WLFC. Second, studies of the main stem Mississippi River have shown that during floods, the sediment transport must increase in the downstream direction [Chatanantavet et al, 2012;Lamb et al, 2012;Nittrouer et al, 2012]. These studies use capacity transport formulations, but any increase in sediment transport rate would require erosion of the bed.…”
Section: The Cover Effect and Supply-limited Channelsmentioning
confidence: 99%